Transcatheter edge-to-edge mitral valve repair in atrial functional mitral regurgitation: insights from the multi-center MITRA-TUNE registry. (15th February 2022) - Popolo Rubbio, Antonio; Testa, Luca; Grasso, Carmelo; Sisinni, Antonio; Tusa, Maurizio; Agricola, Eustachio; De Marco, Federico; Petronio, Anna Sonia; Montorfano, Matteo; Citro, Rodolfo; Adamo, Marianna; Mangieri, Antonio; et al.
Abstract: Background: A-FMR is considered a specific sub-type of secondary MR in patients with atrial fibrillation (AF) and preserved left ventricle ejection fraction (LVEF). Aim of the study was to investigate the acute and mid-term outcomes of transcatheter edge-to-edge mitral valve repair (TMVr) with the MitraClip in atrial functional mitral regurgitation (A-FMR). Methods: The study included patients with A-FMR and concomitant AF who underwent to the MitraClip at 7 Italian Centers. Aim of the study was to assess the safety, efficacy and mid-term cardiovascular outcomes. Results: After reviewing 1153 patients with FMR treated with TMVr from 2009 to 2021, 87 patients (median age 81 years, 61% female) with A-FMR were identified. Technical success was achieved in 97%, 30-day device success in 83% and 30-day procedural success in 80%. All-cause death at 30-day was 5%. Estimated two-year freedom from all-cause death and cardiac death was 60% and 77%, respectively, whereas freedom from all-cause death/heart failure hospitalization was 55%. Residual MR ≤ 2+ was encountered in 89% (n = 47/53) and improvement in NYHA class I/II in 79% (n = 48/61). Post-procedural MR ≥ 2+ (HR 5.400, CI 1.371–21.268) and inter-commissural annular diameter ≥ 35 mm (HR 4.159, CI 1.057–16.363) were independent predictors of all-cause death/heart failure hospitalization during the follow-up. Positive reverse remodeling of left atrium and mitral annular dimensions occurred after TMVr during the follow-up. Conclusions: MitraClip resulted to be a safe and effective option to treat A-FMR in elderly patients. Graphical abstract: The MITRA-TUNE registry: A-FMR characteristics and changes in MR and NYHA class during the follow-up after MitraClip (A) Compared to baseline (34.5% MR 3+ and 65.5% MR 4+), a statistically significant improvement was observed at discharge (70% MR 1+, 28% MR 2+, 2% MR ≥3+, p ≤ 0.001) and at the follow-up (43% MR 1+, 46% MR 2+, 11% MR 3+, p ≤ 0.001). Median echocardiographic follow-up was 371 days [IQR 158–1067 days]. (B) Compared to baseline (17% NYHA II, 71% NYHA III and 12% NYHA IV), a statistically significant improvement was observed at the follow-up (4% NYHA I, 75% NYHA II, 18% NYHA III, 3% NYHA IV, p ≤ 0.001). Median clinical follow-up was 489 days [IQR 242–1033 days]. LVEF = left ventricle ejection fraction; LVEDD = left ventricle end-diastolic diameter; LV = left ventricle; MR = mitral regurgitation; FMR = functional mitral regurgitation; TMVr = transcatheter mitral valve repair; A-FMR = atrial functional mitral regurgitation; MVARC = Mitral Valve Academic Research Consortium; NYHA = New York Heart Association. Unlabelled Image Highlights: Up to 1135 patients with FMR treated in Italy with the MitraClip, 87 (7.6%) fulfilled criteria for A-FMR The MitraClip in A-FMR presented a technical success of 97%, 30-day device success of 83% and procedural success of 80%. Estimated two-year freedom from all-cause death and cardiac death was 60% and 77%. Positive reverse remodeling of LA and mitral annular dimensions occurred after the MitraClip during the follow-up.